The Influence of Javanese Culture on the Decision to Work in Japan Specified Skilled Worker (SSW) Scheme for Vocational High School Graduates in Malang City - Zulqoidah (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The Specified Skilled Worker (SSW) program launched by Japan in 2019 provides significant opportunities for Indonesian vocational high school graduates, particularly in the caregiving and hospitality sectors. However, participation from SMK Negeri 2 Malang remains low despite preparatory classes being offered since 2020. This conceptual research aims to analyze the influence of Javanese cultural values ​​on vocational high school graduates' decisions to work in Japan through SSW, identify cultural barriers, and develop solutions. Using a qualitative approach with a literature review and case studies, the population included graduates of SMK Negeri 2 Malang (2020-2025) involved in the SSW program (approximately 20 alumni, 11 successful), with purposive sampling of tracer study data. Instruments consisted of secondary documents from journals and school records, analyzed using inductive thematic techniques. The results show that Javanese values ​​such as family ties, mutual cooperation, parental responsibility, and Islamic principles significantly hinder migration due to concerns about social harmony. In conclusion, interventions such as family counseling and subsidies are needed to balance cultural preservation with global mobility.